La importancia del liderazgo en empresas constructoras para afianzar su crecimiento sostenible (2023)
The purpose of this work is to analyze the importance of leadership in medium-sized construction companies (SMEs), aimed at strengthening sustainability, which favors their productivity and competitiveness. For the above, the research mainly approached establishing the models, styles, characteristics of organizational leadership, in order to determine the importance they have in the construction sector; so that in this way the processes carried out within the company are more efficient.